Information required for dossiers to support demands for import of high risk plants, plant products and other objects as foreseen in Article 42 of Regulation (EU) 2016/2031. Issue 10 (31st October 2018) - ,; Dehnen‐Schmutz, Katharina; Miret, Josep Anton Jaques; Jeger, Michael; Potting, Roel; Corini, Antonia; Simone, Gabbi; Kozelska, Svetla; Munoz Guajardo, Irene; Stancanelli, Giuseppe; Gardi, Ciro
Abstract : Article 42 of the new Plant Health Law (Regulation (EU) 2016/2031 on protective measures against pests of plants), introduce a concept of "high risk plants, plant products and other objects" in relation to the presence of a pest risk of an unacceptable level for the Union territory, identified on the basis of a preliminary assessment to be followed by a risk assessment. Upon request of the European Commission (EC), the European Food Safety Authority (EFSA) defined the information required and developed a format for the preparation and submission of technical dossiers from third countries to support demands for import of high risk plants, plant products and other objects as foreseen in Article 42(5) of Regulation (EU) 2016/2031. The draft of this Technical Report was circulated to the EFSA Scientific Network for Risk Assessment in Plant health for commenting. The aim of this Technical Report is to enable the applicants to provide in their technical dossiers the information needed by EFSA to perform a Commodity Risk Assessment. The information required concerns: 1) the commodity (characterization of product and the description of the production process); 2) the pests potentially associated with the commodity in the exporting country; 3) the data on phytosanitary mitigation measures and inspections. Instructions on how this information should be presented are also provided.